A Survey on Wearable Internet of Things (IoT) Devices and its Benefits - Sapna, S (International Journal of Computer Sciences and Engineering, 2025)
IoT wearable devices allow non– invading uninterrupted observing of physiological constraints that assist in constant monitoring of fitness and capability of health. Wearable devices are in forms of belts and wrist-bands. IoT applications are used as an application for health and lifestyle monitoring systems and wearable electronics. IoT has come across into numerous technological fields in a faster way. IoT wearable medical devices are emerging to help the affected patients suffering from chronic diseases. Healthcare monitoring, earlier diagnose, personalized treatment is a capable approach of wearable devices. Medical wearable device is a supportable, maintainable and cost-effective advancement in the field of IT. This paper provides the survey on the futures of wearable IoT in healthcare applications